ANALISIS YURIDIS KETIDAKSINKRONAN PRAKTIK SURAT KUASA KHUSUS BERKELANJUTAN DENGAN PASAL 44 AYAT (1) HURUF A UNDANG-UNDANG MAHKAMAH AGUNG - Astria Rosliana Dewi; Kristina Uba Payon; Grardus Jackson Ndu adu; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
A special power of attorney is a formal instrument that determines the legal validity of an advocate's representation before the court. Legal practice in Indonesia commonly shows that advocates use a single power of attorney continuously from the first-level court through the cassation stage at the Supreme Court. However, Article 44 paragraph (1) letter a of Law Number 14 of 1985 on the Supreme Court explicitly requires that a representative must be